"Garden of Eden" or "Paradise of delight"? The Septuagint's rendering of ??? in the book of Genesis - H. Ausloos (Acta Theologica)
Within the first chapters of the book of Genesis, the “paradise” is located in “Eden”.  At least, this is how the majority of modern translators interpret the Hebrew term ??? . However, within the Hebrew text of Genesis 2-3, the term “Eden” seems to be used with a double entendre: on the one hand, the author intended to use the term ??? as a toponym; on the other hand, in his word choice, it appears that the author aimed to characterise the specific nature of the “Eden” as a place of plenty and wealth. Through an analysis of the equivalents used in the Greek version of the Creation narrative, it is argued that the Septuagint translator of Genesis, alternately transliterating and translating ??? , and therefore not manifesting him-/herself as a “consistent” translator, succeeded in producing a faithful rendering of the term.